The jurisdictional games of immigration policing: Barcelona’s fight against unauthorized street vending - Moffette, David (Theoretical criminology, 2020)
The article maps out the multilayered legal governance of immigrant street vendors in Barcelona. The case study is used to develop the literature on crimmigration by suggesting better ways to account for the dynamic, asymmetric, and uneven legal intersections at play in immigration governance. Questioning the idea of a merger between immigration law and criminal law that scholars of crimmigration often imply, the article suggests that it is the heterogeneity and distinction between various legal regimes that is most productive and problematic in the governing of immigrants. The article offers the concept of interlegal jurisdictional games as an alternative point of entry to study these dynamics.